Reversible operation of a pressurized solid oxide cell stack using carbonaceous gases. (April 2019) - Jensen, S.H.; Langnickel, H.; Hintzen, N.; Chen, M.; Sun, X.; Hauch, A.; Butera, G.; Clausen, L.R.
Highlights: 30-cell solid oxide cell stack operated at pressures up to 18.7 bar. Conversion of carbonaceous gases in both fuel cell and electrolysis mode. Electro-catalytic formation of 18% methane in electrolysis mode. Promising operation stability with a methane rich gas in fuel cell mode. Abstract: Low energy conversion efficiency and high storage costs still hamper a successful implementation of sustainable energy systems. Recent theoretical studies show that reversible electrochemical conversion of H2 O and CO2 to CH4 inside pressurized solid oxide cells combined with subsurface storage of the produced gases can facilitate seasonal electricity storage with a round-trip efficiency reaching 80% and a storage cost below 3 ¢/kWh. Here we present test results with a 30-cell SOFCMAN 301 stack operated with carbonaceous gases at 18.7 bar and 700 °C in both electrolysis and fuel cell mode. In electrolysis mode the CH4 content in the stack outlet gas increased from 0.22% at open circuit voltage to 18% at a current density of −0.17 A cm −2 . The degradation observed by scanning electron microscopy studies correlate well with the observed electrochemical stack degradation. The degradation rates in both fuel cell and electrolysis mode were comparable to previously reported SOFCMAN stack degradation rates measured at ambient pressure operation with H2 /H2 O gas mixtures.